Urbanization and Economic Growth in Indonesia : Good News, Bad News, and (Possible) Local Government Mitigation - Lewis, Blane D. (Taylor and Francis, 2013)
Time series analysis for Indonesia over the period 1960-2009 suggests that the level of urbanization is positively associated with economic growth but that the rate of change of urbanization is negatively correlated with growth of economic output. A sub-national dynamic panel investigation provides additional evidence of the positive and negative level and rate effects, respectively. The panel analysis also implies that the harmful impact of urban population growth is linked to insufficient local public infrastructure spending. Local governments that invest more heavily in infrastructure are better able to cope with the apparent detrimental effects of rapid urbanization on economic growth.